RAPD Characterization of Pseudomonas species identified from clinical samples - Pethannan, Rajarajan; Kuppuswamy, Amudha Chinnaiah; Kirubakaran Vinod Kumar, Rajani Gupta,; Vrashabha Jawai, Swati Baliyan, Guru Prasad, (Recent Research in Science and Technology)
Pseudomonas aeruginosa is the most common dreadful pathogenic gram negative bacilli responsible for nosocomial infections among hospital patients especially in developing countries. In the present study P. aeruginosa isolated from various clinical samples and evaluated for their variability and genetic relationship using PCR based Randomly Amplified Polymorphic DNA (RAPD) technique. A total of 30 different samples from patients with wounds, ear infection, respiratory tract, nasal infection and urine infection were collected from various hospitals and diagnostic centers in Bangalore. The samples included pus swabs, wound discharge, sputum and blood. These samples were subjected to P. aeruginosa isolation using selective media and characterization using biochemical tests. Further genetic relationship was determined using RAPD technique. A total of 7 were isolated and characterized biochemically and identified belonging to P. aeruginosa. Cluster analysis and phylogenetic tree reveal close relatedness between P. aeruginosa strain P1, P3, P4, P5 and P6 but distantly related to the P2 and P7. This indicates that the infection due to P. aeruginosa is caused by diverse as well as closely related clones circulating in the study health care centers. This demands further investigation through prospective studies with a larger number of patients. This will aid suggesting efficient and sustained control measures and antibiotic policy in study area